2019
DOI: 10.1039/c8nr10332a
|View full text |Cite
|
Sign up to set email alerts
|

On the decay time of upconversion luminescence

Abstract: Numerical simulations based on rate-equation models were performed to investigate how the upconversion luminescence decay is affected by the lifetimes of intermediate states, energy transfer, and cross-relaxation processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 40 publications
3
58
0
Order By: Relevance
“…30 The increased ETU probability demonstrated by the Yb 3+ decay curves should result in a shorter decay time of the 1 I 6 level. 31 This is evidenced by the results in Fig. 4; the rise and decay times of the 1 I 6 and 1 D 2 Fig.…”
Section: Resultsmentioning
confidence: 67%
“…30 The increased ETU probability demonstrated by the Yb 3+ decay curves should result in a shorter decay time of the 1 I 6 level. 31 This is evidenced by the results in Fig. 4; the rise and decay times of the 1 I 6 and 1 D 2 Fig.…”
Section: Resultsmentioning
confidence: 67%
“…This underlying physical process is the cause behind the slightly increased PSL lifetimes and serves as an independent check behind the feasibility of the measured lifetimes. Although it is not a similar optical process, such phenomena had been demonstrated in the field of upconversion luminescence, where multiple underlying physical processes resulted in decay times that were greater than the natural decay times of the lanthanide dopants used 58 . We also acknowledge that measuring PSL's lifetime is challenging.…”
Section: Discussionmentioning
confidence: 91%
“…Although it is not a similar optical process, such phenomena had been demonstrated in the field of upconversion luminescence, where multiple underlying physical processes resulted in decay times that were greater than the natural decay times of the lanthanide dopants used. 58 We also acknowledge that measuring PSL's lifetime is challenging. In the literature it has been reported that the lifetime of Eu 2+ in the PSL process is about 1 μs, 25 shorter than what we report here.…”
Section: G Suitability For 2d Readoutsmentioning
confidence: 99%
“…Through successive energy transfer steps from three (or more) Yb 3+ ions to Tm 3+ , the conversion process from low-energy near-infrared photons to high-energy visible photons can be realized. In principle, the decay time extracted from the upconversion luminescence decay profile generally cannot be interpreted as the intrinsic lifetime of the upconversion luminescence emitting state [ 25 ]. Instead, it is an overall temporal response of the whole upconversion system to the excitation function, influenced by the sensitizer’s excited-state intrinsic lifetime and the effects of energy transfer [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In principle, the decay time extracted from the upconversion luminescence decay profile generally cannot be interpreted as the intrinsic lifetime of the upconversion luminescence emitting state [ 25 ]. Instead, it is an overall temporal response of the whole upconversion system to the excitation function, influenced by the sensitizer’s excited-state intrinsic lifetime and the effects of energy transfer [ 25 ]. Since these NIR-II excited upconversion processes do not rely on the Yb 3+ sensitizer with long-lived state, the upconversion luminescence decay would not be influenced by the long excited-state lifetime of the sensitizers and the effect of energy transfer.…”
Section: Resultsmentioning
confidence: 99%